Penerapan Media Pembelajaran Realia dalam Meningkatkan Pemahaman Siswa Kelas X pada Materi Dinamika Hidrosfer di SMAN 15 Padang - Fitria Ramadani; Momon Dt Tanamir; Slamet Rianto (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research is motivated by the lack of variety of media in learning. Students are less motivated in the teaching and learning process and there are obstacles in the delivery of learning material and are often found in learning outcomes that are < from KKM. This study identified and analyzed data about the application of realia learning media to improve students' understanding of the dynamics of the hydrosphere class X at SMAN 15 Padang. The use of realia learning media turned out to make students more active in responding to the media applied by the researcher. The type of research used is a quasi-experimental research type. The population in this study amounted to 818 students with a total of 9 classes X.E class. While the sample in the research class X.E 1 control class, X.E 5 experimental class. The data analysis technique used was descriptive statistical technique and inferential statistical analysis. Based on the research data and discussion that has been described, it is concluded that based on the results of the t test of 3,120 with a significant value of 0.003 <0.05, it means that Ha is accepted so that the data can be concluded that the application of realia learning media can improve students' understanding of the dynamics of the hydrosphere class X at SMAN 15 Padang.AbstrakPenelitian ini dilatarbelakangi oleh kurangnya variasi media dalam pembelajaran. Siswa kurang termotivasi dalam proses belajar mengajar dan terdapat kendala dalam penyampaian materi pembelajaran serta sering dijumpai hasil belajar yang < dari KKM. Penelitian ini mengidentifikasi dan menganalisis data tentang penerapan media pembelajaran realia untuk meningkatkan pemahaman siswa tentang dinamika hidrosfer kelas X di SMAN 15 Padang. Penggunaan media pembelajaran realia ternyata membuat siswa lebih aktif dalam menanggapi media yang diterapkan peneliti. Jenis penelitian yang digunakan adalah jenis penelitian eksperimen semu. Populasi dalam penelitian ini berjumlah 818 siswa dengan jumlah 9 kelas kelas X.E. Sedangkan sampel penelitian adalah kelas X.E 1 kelas kontrol, X.E 5 kelas eksperimen. Teknik analisis data yang digunakan adalah teknik statistik deskriptif dan analisis statistik inferensial. Berdasarkan data penelitian dan pembahasan yang telah diuraikan, disimpulkan bahwa berdasarkan hasil uji t sebesar 3.120 dengan nilai signifikansi 0,003 < 0,05 berarti Ha diterima sehingga dapat disimpulkan bahwa data penerapan media pembelajaran realia dapat meningkatkan pemahaman siswa tentang dinamika hidrosfer kelas X di SMAN 15 Padang.